ショウワキチ カンソクトウ デ 35 ネンカン シヨウ シタ コウゾウ ガスケット ノ カタサ チョウサ - 高橋, 弘樹; タカハシ, ヒロキ; 半貫, 敏夫; ハンヌキ, トシオ; 鮎川, 勝; アユカワ, マサル; 武智, 義加; タケチ, ヨシカ; 大塚, 徹; オオツカ, トオル; Takahashi, Hiroki; Hannuki, Toshio; et al. (2014)
P(論文) 第43次日本南極地域観測隊越冬隊において,昭和基地の観測棟で35 年間使用された構造ガスケットの硬さ試験を行った.新品の構造ガスケットを用いて硬さ試験を行い,その結果を初期値とした.紫外線が多く当たる北西面の構造ガスケットは,南東面の構造ガスケットに比べて劣化が進んでいた.屋外側と屋内側の劣化の程度は,ほぼ同じであった.観測棟で35 年間使用した構造ガスケットは,新品の構造ガスケットに比べて,硬さが1 割増加した程度であり,大きな亀裂などは見られなかった.これらより,この構造ガスケットは今後も昭和基地で継続して使用可能であると考えられる. A structural gasket at the observation hut in Syowa Station has been in use for 35 years. We studied the hardness of the original structural gasket during the 43rd Japanese Antarctic Research Expedition. We tested that of the new article, and the results are assumed to be an initial value. The structural gasket at the northwest section of the station deteriorated to a greater extent than did the structural gasket at the southeast section, because of the former's exposure to ultraviolet radiation. The exterior and interior components of the northwest structural gasket show similar degrees of degradation. This structural gasket has hardened by 10 % relative to the new structural gasket. The 35-year-old structural gasket contains no large cracks, indicating its suitability for continual use. departmental bulletin paper